Analisis Pola Produktivitas Penulis Artikel Bidang Perpustakaan Dan Informasi Di Indonesia : Suatu Kajian Bibliometrika - Wahyudi, Agus; Kustiyo, Aziz; Basuki, Sulistyo (Perpustakaan IPB, 2015)
This study examines the productivity of the authors in the field of library and information science in Indonesia during the year of 2001-2010 by using Lotka’s law. The population of this study are all kinds of scientific articles contained in the journal library and information science in which the journal is registered in PDII-LIPI databases and published between the years 2001 to 2010. Assessment author's participation was done by using 'straight count'. The sampling technique used is saturated sample. Journals in accordance with the criteria of research as much as 24, 1085 articles written by 1018 authors. Due to this research used 'straight count' only 547 authors counted. Obtained the results of the calculation of the value of n worth 1,92 and C 0,6172. The finding conclude, in the year 2001-2010 the number of certain writers that contribute one article is 61.72% of the total number of authors. Test results showed that the value Dmaks smaller than the critical value, this means that the productivity distribution author library and information science in Indonesia year of 2001-2010 in accordance with the argument of Lotka’s law. It is known that the productive author works as a lecturer/librarians derived from the college environment.Keywords: Library and Information Science, Bibliometrics, Lotka’s Law